2016
DOI: 10.3329/bjms.v15i3.30200
|View full text |Cite
|
Sign up to set email alerts
|

Dental intervention perspective: Anatomical Variation of Mental and Mandibular Foramen in Selected Malay Patients

Abstract: Abstract:Background: Anatomical structures of head are essential to carry out almost all of dental procedures.In this regard to study the variation of mental and mandibular foramens are prerequisite for the intervention of clinical dentistry. The study was undertaken to determine the anatomical position of the mental foramen (mF) and mandibular foramen (MF) and their relationship. Methods and Methods: Eighty-seven selected Malay patients were examined at Universiti Kebangsaan Malaysia Dental Clinics in which 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…Therefore, for proper anesthesia, a clinical reference point is required. Previous studies indicated that MF was positioned below the OP in the range of 80.4% to 19.87% in African, Thai, Zimbabwean, Brazilian, and East Indian populations as described in Table 3 ( 5 , 7 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 ). Different methodologies or ethnicity lead to this wide range of results.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Therefore, for proper anesthesia, a clinical reference point is required. Previous studies indicated that MF was positioned below the OP in the range of 80.4% to 19.87% in African, Thai, Zimbabwean, Brazilian, and East Indian populations as described in Table 3 ( 5 , 7 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 ). Different methodologies or ethnicity lead to this wide range of results.…”
Section: Discussionmentioning
confidence: 97%
“…The direct method using skulls or radiographic method was used to determine the relative location of MF with the OP ( 5 , 7 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 ). Although the skull provides direct observation, when the investigation is based on an “imaginary line” without systematic methodology, this approach makes such valuable data as direct observation subjective and unrepeatable.…”
Section: Discussionmentioning
confidence: 99%
“…The morphometric measurements using dried skulls have unique significance over other methods such as radiological or intraoperative procedures as the former gives a whole integrated morphology of the foramen/notches 23 . The importance of morphometric study of the SOF/SON and IOF gains a special attention and popularity in invasive surgical approaches which are having limited visibility 24,25 .…”
mentioning
confidence: 99%